Surgical Treatment of Iatrogenic Low Variety Anal Stenosis with Diamond Flap Anoplasty – A Prospective Study (Journal of Shaheed Suhrawardy Medical College, 2022)
Background: Anal stenosis results from loss of anoderm with subsequent fibrosis and scarring of underlying tissue. The condition represents a technical challenge in terms of surgical management. It is a serious complication of anorectal surgery, most commonly seen after surgical haemorrhoidectomy. However, stenosis can also occur after perianal circumferential burn due to application of herbal medicine by village doctors.Objective: This study was conducted to see the outcome of diamond-flap anoplasty for the treatment of moderate to severe anal stenosis.Patients and interventions: Unilateral diamond flaps anoplasty was performed for moderate to severe anal stenosis. Final anal calibre of 25 to 26 mm was targeted. The demographic characteristics, causes of anal stenosis, number of previous surgeries, anal stenosis severity, postoperative complications and the time of return to work were recorded.Results: From July 2012 to January 2017, 18 patients (12 males, 67% and 6 female patients, 33%) with a mean age of 34 years (range, 25-52) were treated. 15 of the patients had a history of previous haemorrhoidectomy and 3 had circumferential perianal chemical burn due to application of herbal medicine by village doctors. Five patients (28%) had moderate anal stenosis and 13 (72%) had severe anal stenosis. Preoperative, intraoperative, and 12-month postoperative anal calibration values were 9 ± 3 mm (range, 5-15), 25 ± 0.75 mm (range, 24- 26), and 25 ± 1 mm (range, 23-27). The clinical success rate was 98.9%. No severe postoperative complications were observed.Conclusion: Diamond-flap anoplasty is a highly successful method for the treatment of anal stenosis caused by previous haemorrhoidectomy and perianal circumferential chemical burn by herbal medicine.J Shaheed Suhrawardy Med Coll 2020; 12(2): 67-71